Are Parents Patient? The Influence of Parenting Role Salience and Parental Status on Impatience - Li, Yuanyuan J.; Liu, Yuanyuan (Frontiers in Psychology, 2018)
In the classic intertemporal discounting task (Thaler, 1981), individuals make tradeoff decisions between smaller-sooner and larger-later monetary rewards. We explored how parental role salience and parental status influences individual’s choice between smaller-sooner and larger-later choices. Parental role salience is manipulated among both parents and non-parents in this research. Our results show a significant interaction between parental status and manipulated parental role salience. Specifically, we found that parents are more impatient than non-parents. Additionally, non-parents become more impatient after parental role salience manipulation, similar to parents. Theoretical implications of our findings are discussed.